Association and linkage analysis of COL1A1 and AHSG gene polymorphisms with femoral neck bone geometric parameters in both Caucasian and Chinese nuclear families - Jiang Hui; Lei Shu-feng; Xiao Su-mei; Chen Yuan; Sun Xiao; Yang Fang; Li Li-ming; Wu Shan; Deng Hong-wen (Acta Pharmacologica Sinica, 2016)
Aim: To simultaneously investigate the contribution of the alpha 1 chain of collagen type 1 (COL1A1) and alpha2-HS-glycoprotein (AHSG)genes to the variation of bone geometric parameters in both Caucasians and Chinese. Methods: Six hundred and five Caucasian individuals from 157 nuclear families and 1228 Chinese subjects from 400 nuclear families were genotyped at the AHSG-SacI, COL1A1-PCOL2andSp1 polymorphisms using polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP). 5 FN bone geometric parameters were calculated based on bone mineral density and bone area of femoral neck (FN) measured by dual energy X-ray absorptiometry. Population stratification, total family association, within-family association, and linkage tests were performed by the quantitative transmission disequilibrium test program. Results: The t-test showed the significant differences of all bone geometric phenotypes (except ED) between Caucasians and Chinese in the offspring using both unadjusted and adjusted (by age, height, weight, and gender) data. In Caucasians, we found significant within-family association results between the COL1A1-Sp1 polymorphism (rs1800012) and cross sectional area (CSA), cortical thickness (CT), endocortical diameter (ED), buckling ratio (BR) (P = 0.018, 0.002, 0.023, and 0.001, respectively); the COL1A1-Sp1 polymorphism also detected significant linkage with BR (P = 0.039). In the population of China, the within-family associations between the COL1A1-PCOL2polymorphism (rs1 107946) and CT, BR were significant (P= 0.012 and 0.008, respectively). Furthermore, evidence of linkage were observed between the AHSG-SacI polymorphism (rs4918) and CT, BR (P= 0.042 and 0.014, respectively) in Caucasians, but not in Chinese. Conclusion: Our results suggest that the COL1A1gene may have significantly association with bone geometry in both Caucasians and Chinese, and the AHSG gene may be linked to bone geometry in Caucasians, but not in Chinese. This study represents our first efforts on investigating the importance of the COL1A1 andAHSG genes on bone geometry in both Caucasians and Chinese.